PENGARUH COMMUNITY SOCIAL RESPONSIBILITY (CSR) TERHADAP CITRA PERUSAHAAN - Triwilopo, Sendi (Jurnal Bisnis Darmajaya, 2016)
This study isbased on the Theory of Organizational Image Management by Joseph Eric Massey and apply the deduction-quantitative approach. The theory analysis is basiclyfocused to the dialogic interactions betweencompany organizationsand their stakeholders . In turn, the images wanted by the organizational parties will beco-created together with their stakeholders in the activity of interactive communications .Such matter can be studied at the activity of Corporate Social Responsibilty (CSR) realized by PT. Perkebunan Nusantara (Persero) Lampung on establishing the business partnership.As effort to test the theory, the research results indicate that to manage the company image can be optimally reached by applying the concept of co-create together with stakeholders.Other finding is the credibility of the communicators who handle the function of CSR have an effects / influences to the company imageKeyword: Image Management, co - create